Public-administrative mechanisms for quality of higher medical education in the context of reforms and instability - Moroz, O. (Національний технічний університет "Харківський політехнічний інститут", 2025)
This paper analyzes the impact of public-administrative mechanisms on the quality of higher medical education in Ukraine under conditions of reform and war. Using data from Times Higher Education (THE) Rankings and KROK-1 examination results, it reveals that while clinical competence and exam performance remain stable, insufficient research activity limits international ranking presence. The paper highlights legislative foundations of continuous professional development and compares Ukrainian and European approaches to research integration. Recommendations focus on enhancing research-based learning and publication incentives to strengthen global academic standing.
Keywords: higher medical education; public-administrative mechanisms; quality; international ranking; professional development; research integration; global academic standing